(untitled) - Kreppel, Amie (Cambridge, 2002)
This book examines the impact of increased legislative power and political authority on the internal development of the European Parliament and the supranational party group system. This is done through an analysis of changes in the hierarchical structures that regulate the internal organization of both the European Parliament as a whole and the individual party groups. In addition, the changing pattern of coalition formation between party groups across time and legislative procedure is analyzed.
Keywords: Political parties,Coalitions,Đảng phái chính trị,Liên Minh; European Union countries,Liên minh Châu Âu